Determinants of maternal near miss among women in Northeast Iran: A facility-based case-control study - Sedigheh Abdollahpour; Hamid Heidarian Miri; Elham Azmoude; Mahsa Pieranj; Maryam Kabirian (Iranian Journal of Nursing and Midwifery Research, 2023)
Background: The investigation of Maternal Near-Miss (MNM) risk factors is important for the global reduction of maternal mortality. This study aimed to identify the determinants of MNM among pregnant women in northeastern Iran. Materials and Methods: A prospective case-control study was conducted on 250 women referred to the maternity ward of Nohom-e-Dey hospital in Torbat-e Heydarieh, Iran, from June 2018 to May 2020. Applying the criteria of the World Health Organization tool, near-miss mothers were taken as cases, and mothers with normal obstetric outcomes were selected as controls with convenience sampling. Logistic regression models using Stata version 14.0 and odds ratios (95% confidence intervals) were reported. Results: A total of 123 MNM cases and 127 controls were included in the study. The multiple logistic regression represented that having had previous abortion, living in rural or urban areas, whether the mother went through C/S or vaginal delivery and level of prenatal education were associated with MNM. Besides, having experienced chronic medical diseases during pregnancy had the strongest association with MNM, and next were complications during childbirth and neonatal outcomes which were associated with MNM, although in terms of statistical association, only the first two mentioned factors were statistically significant. Conclusions: Determinants of MNM could be experiencing chronic medical disorders during maternal complications. Health providers need to carefully manage past medical history and adverse perinatal outcomes, especially in pregnant women who live in rural areas. Encouraging mothers to attend pregnancy training classes is effective in reducing MNM.